Identification and characterization of a new cognitive enhancer based on inhibition of insulin-regulated aminopeptidase - Albiston, Anthony L; Morton, Craig J; Ng, Hooi Ling; Pham, Vi; Yeatman, Holly R; Ye, Siying; Fernando, Ruani N; De Bundel, Dimitri; Ascher, David B; Mendelsohn, Frederick A O; Parker, Michael W; Chai, Siew Yeen (The FASEB journal, 2008)
Approximately one-quarter of people over the age of 65 are estimated to suffer some form of cognitive impairment, underscoring the need for effective cognitive-enhancing agents. Insulin-regulated aminopeptidase (IRAP) is potentially an innovative target for the development of cognitive enhancers, as its peptide inhibitors exhibit memory-enhancing effects in both normal and memory-impaired rodents. Using a homology model of the catalytic domain of IRAP and virtual screening, we have identified a class of nonpeptide, small-molecule inhibitors of IRAP. Structure-based computational development of an initial "hit" resulted in the identification of two divergent families of compounds. Subsequent medicinal chemistry performed on the highest affinity compound produced inhibitors with nanomolar affinities (K(i) 20-700 nM) for IRAP. In vivo efficacy of one of these inhibitors was demonstrated in rats with an acute dose (1 nmol in 1 microl) administered into the lateral ventricles, improving performance in both spatial working and recognition memory paradigms. We have identified a family of specific IRAP inhibitors that is biologically active which will be useful both in understanding the physiological role of IRAP and potentially in the development of clinically useful cognitive enhancers. Notably, this study also provides unequivocal proof of principal that inhibition of IRAP results in memory enhancement.